Improving Food Security in Arab Countries - World Bank; FAO; IFAD (World Bank, Washington, DC, 2016)
This joint working paper lays out a rationale and strategic framework for improving food security and managing food-price shocks in the Arab countries. The paper does not provide country specific policy and project recommendations. Such recommendations will follow from the country by country application of the framework, taking into account each country's political and cultural preferences, resource endowments, and risk tolerance. In 2007 and the first half of 2008, a sharp rise in agricultural commodity and food prices triggered grave concerns about food security, malnutrition and increased poverty throughout the world. While the threat of a prolonged food-price shock receded with falling energy and commodity prices and a weakening global economy in the second half of 2008, many factors underlying the volatility in food prices appear here to stay and will require careful management if the world is to avoid future food-price shocks. This paper suggests three critical strategies that, together, can serve as pillars to help offset future vulnerability to price shocks: a) strengthen safety nets, provide people with better access to family planning services, and promote education; b) enhance the food supply provided by domestic agriculture and improve rural livelihoods by addressing lagging productivity growth through increased investment in research and development; and c) reduce exposure to market volatility by improving supply chain efficiency and by more effectively using financial instruments to hedge risk.